Interplay between Kondo and Majorana interactions in quantum dots - Cheng, Meng; Becker, Michael; Bauer, Bela; Lutchyn, Roman (Physical Review X, 2014)
We study the properties of a quantum dot coupled to a topological superconductor and a normal lead and discuss the interplay between Kondo-and Majorana-induced couplings in quantum dots. The latter appears due to the presence of Majorana zero-energy modes localized, for example, at the ends of the onedimensional superconductor. We investigate the phase diagram of the system as a function of Kondo and Majorana interactions using a renormalization-group analysis, a slave-boson mean-field theory, and numerical simulations using the density-matrix renormalization-group method. We show that, in addition to the well-known Kondo fixed point, the system may flow to a new fixed point controlled by the Majoranainduced coupling, which is characterized by nontrivial correlations between a localized spin on the dot and the fermion parity of the topological superconductor and the normal lead. We compute several measurable quantities, such as differential tunneling conductance and impurity-spin susceptibility, which highlight some peculiar features characteristic to the Majorana fixed point